Progress on sacral neuromodulation in treatment of pelvic floor dysfunction - WANG Ji⁃peng; YAN Ze⁃hao; ZHANG Jiong; WANG Xin⁃hao; ZHANG Yao⁃guang (Chinese Journal of Contemporary Neurology and Neurosurgery)
Sacral neuromodulation (SNM) as an advanced form of neuromodulation technique, which has demonstrated significant efficacy in alleviating clinical symptoms for patients with pelvic floor dysfunction (PFD) who do not respond to conventional treatments. This paper provides a comprehensive review of the application and progress of SNM in the treatment of PFD. It covers its historical development, mechanisms of action, clinical applications, optimization of stimulation parameters, and several technological innovations that have facilitated its clinical adoption. The aim is to promote wider clinical application of SNM and offer more precise treatment options for patients.